Modelagem e controle LQR aplicado a um condicionador de energia - Kanieski, João Marcos (2010)
This work presents the development of a control system, based on optimum control theory, applied for an energy conditioner device, where it is included, on its model, the dynamics imposed by the grid voltages at the connection point. The power conditioner system acts as a quality energy controller, supplying reactive and non-active power, even under unbalance linear and non-linear loads. Moreover, the present work proposes a solution for reducing the phase deviation problem inserted by a second order low-pass filter, used for mitigating the aliasing problem, showing an instrumentation alternative to solve this problem. The energy conditioner topology uses a three-phase three-legs shunt voltage source inverter (VSI). The current reference generation is obtained from a recently proposed method, based on optimum filtering theory. This algorithm, together with the chosen control strategy, allows to obtain a satisfactory compromise between transient response and perturbation rejection on the generation of the reference signals and control of the whole system. At the end of this work, a comparison among the proposed control structure and two others controllers, namely Proportional-Integral (PI) and Linear Quadratic Regulator with Integral action (LQRI), is made in order verify the efficacy of the developed methodology. On this comparison, its presented the performance of these 3 controllers, considering several performance criteria: reference tracking, voltage and current harmonic distortion as well as robustness of the system under grid impedance changes.